Ectopic Tertiary Lymphoid Tissue in Inflammatory Bowel Disease: Protective or Provocateur? - McNamee, Eóin N.; Rivera-Nieves, Jesús (Frontiers in Immunology, 2016)
Organized lymphoid tissues like the thymus first appeared in jawed vertebrates around 500 million years ago and have evolved to equip the host with a network of specialized sites, strategically located to orchestrate strict immune-surveillance and efficient immune responses autonomously. The gut-associated lymphoid tissues (GALT) maintain a mostly tolerant environment to dampen our responses to daily dietary and microbial products in the intestine. However, when this homeostasis is perturbed by chronic inflammation, the intestine is able to develop florid organized tertiary lymphoid tissues (TLT), which heralds the onset of regional immune dysregulation. While TLT are a pathologic hallmark of Crohn’s disease (CD), their role in the overall process remains largely enigmatic. A critical question remains; are intestinal TLT generated by the immune infiltrated intestine to modulate immune responses and rebuild tolerance to the microbiota or are they playing a more sinister role by generating dysregulated responses that perpetuate disease? Herein we discuss the main theories of intestinal tertiary lymphoid tissue neogenesis and focus on the most recent findings that open new perspectives to their role in inflammatory bowel disease.